BELAJAR MENAVIGASI KETEGANGAN STRATEGIS: PERAN INTERAKSI SOSIAL DALAM MENGEMBANGKAN ENTREPRENEURIAL PARADOX MINDSET (STUDI KASUS KOMUNITAS TDA MAKASSAR) - Muhammad Taufan Gunawan; Andi Tenri Ellyana Haris; Samsinar Samsinar (STKIP Pesisir Selatan, 2026)
Main Objectives: This study aims to explore how informal entrepreneurial communities, specifically Tangan Di Atas (TDA) Makassar, foster an Entrepreneurial Paradox Mindset (EPM) among early-stage entrepreneurs operating outside formal startup accelerator ecosystems. Background Problems: Early-stage entrepreneurs face persistent strategic paradoxes requiring specific cognitive capabilities to navigate. However, empirical research examining EPM development within informal social networks remains limited, particularly in Eastern Indonesia where venture capital access and institutional support are constrained. Novelty: This study identifies the mechanism of